Cost-effectiveness of bortezomib for multiple myeloma: a systematic review - Chen W; Yang Y; Chen Y; Du F; Zhan H (Dove Medical Press, 2016)
Wendong Chen,1 Yicheng Yang,2 Yi Chen,3 Fen Du,3 Huan Zhan3 1Normin Health, Toronto, ON, Canada; 2Xian Janssen, Beijing, People's Republic of China; 3Normin Health Changsha Representative Office, Changsha, People's Republic of China Objectives: To review published cost-effectiveness analyses (CEA) assessing bortezomib (BTZ) for multiple myeloma (MM) and explore possible bias affecting the cost-effectiveness of BTZ. Methods: Literature was searched for published CEAs assessing BTZ or BTZ-containing regimens for MM from 2003 to 2015. The reported incremental cost-effectiveness ratios (ICER) were adjusted by 2014 country-specific gross domestic product per capita (GDPPC) to compare the cost-effectiveness threshold of the World Health Organization (3 GDPPC per gained quality-adjusted life year [QALY]). Results: A total of 17 published CEAs were included in this review. When compared to non-BTZ treatments, BTZ-containing regimens were cost-effective for induction treatment prior to stem cell transplantation (SCT) in Canada, Poland, and Germany (ICER per QALY: 0.9299–2.254 GDPPC). BTZ/melphalan/prednisolone (VMP) was cost-effective for previously untreated and SCT-ineligible MM patients when compared to melphalan plus prednisolone (MP), melphalan/prednisone/lenalidomide with lenalidomide maintenance, and cyclophosphamide/thalidomide/dexamethasone (CTD) (ICER per QALY: dominant to 2.374 GDPPC) in Canada, UK, and USA. BTZ was cost-effective for relapsed/refractory MM when compared to best supportive care (ICER per life year: 0.9317–1.8210 GDPPC) in the UK and the USA, thalidomide in USA (0.5178 GDPPC/LY), and dexamethasone (DEX) in four Nordic countries (€54,451–€81,560/QALY). However, the cost-effectiveness for VMP versus MP plus thalidomide (MPT) and continuous lenalidomide (LEN) plus low-dose DEX (RD) for previously untreated and SCT-ineligible MM patients and BTZ versus LEN/DEX for relapsed/refractory MM patients could be unreliable because of the bias associated with model design and the indirect comparisons of treatment effects. Conclusion: Published CEAs suggested that BTZ or BTZ-containing regimens were cost-effective when compared to most non-BTZ treatments for MM. However, the conflicting cost-effectiveness for VMP versus MPT for previously untreated and SCT-ineligible MM and BTZ versus LEN/DEX for relapsed/refractory MM needs more robust evidence for further clarification. Keywords: cost-effectiveness, bortezomib, multiple myeloma, systematic review